2285. Burden of Invasive and Non-Invasive Group B Streptococcal Infections in Hospitalized Adults, Louisville, Kentucky: A Large Population-Based Study. (26th November 2018) - Peyrani, Paula; Ramirez, Julio; Quinn, Angela; Swerdlow, David L
Abstract: Background: Although Group B Streptococcus (GBS) has been recognized as an important cause of infections in adults, most studies have concentrated on patients with invasive disease. CDC estimates that there are >25, 000 adult invasive cases in the United States/year. The objective of this study was to determine the burden of invasive and noninvasive GBS infections in hospitalized patients in Louisville, KY with the goal of determining the total burden of GBS infections in the United States. Methods: We conducted a population-based, observational study of all hospitalized adults with GBS isolated from cultures and clinical evidence of active infection from 2014 to 2016 in a well-defined catchment area. Data regarding demographics, medical history, infection sites and microbiology were extracted from medical records. If GBS was isolated from more than one clinical site, the most invasive or deepest site was considered the primary infected site. Results: Of 1428 GBS isolations 352 were considered colonizations therefore 1076 infections were included; Fifty-one percent were males and the median age was 52 years. Twenty-four percent were black and 2% Hispanic. Sixty-six (6%) presented from a nursing home. The median length of hospital stay was 5.2 days and 31 (3%) died. Patients had the following comorbidities: 627 (59%) diabetes, 220 (21%) renal disease, 221 (21%) coronary artery disease, and 154 (14%) peripheral vascular disease. In 642 patients (60%) GBS was the only organism isolated (monomicrobial) and in 320 (30%) GBS was isolated from more than one clinical site. Two hundred and twelve (20%) of patients had isolates from normally sterile sites (invasive). The primary site of infection included 425 (39%) skin and soft tissue, 252 (23%) urinary, 173 (16%) bone or joint, 115 (11%) from blood, 57 (5%) respiratory, 26 (2.4%) cardiovascular, and 25 (2.3%) abdominal. Conclusion: To our knowledge, this is the first study to determine the total burden of both invasive and noninvasive GBS disease among adult hospitalized patients in the United States. Our results suggest that only 20% of cases are invasive indicating that the burden of GBS is up to five times higher than estimates based on invasive infections. Disclosures: P. Peyrani, Pfizer Inc.: Employee, Salary. A. Quinn, Pfizer Inc.: Employee, Salary. D. L. Swerdlow, Pfizer Inc.: Employee and Shareholder, Salary.